2023
DOI: 10.3390/biomedicines11102712
|View full text |Cite
|
Sign up to set email alerts
|

The Modulation Effect of a Fermented Bee Pollen Postbiotic on Cardiovascular Microbiota and Therapeutic Perspectives

Laura-Dorina Dinu,
Florentina Gatea,
Florentina Roaming Israel
et al.

Abstract: Hypertension is a frequent comorbidity in patients with heart failure; therefore, blood pressure management for these patients is widely recommended in medical guidelines. Bee pollen and postbiotics that contain inactivated probiotic cells and their metabolites have emerged as promising bioactive compounds sources, and their potential role in mitigating cardiovascular (CV) risks is currently being unveiled. Therefore, this preliminary study aimed to investigate the impact of a lactic-fermented bee pollen postb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
(94 reference statements)
1
3
0
Order By: Relevance
“…Recent studies on fermented foods by the LAB group have also reported the presence of polyphenols (4-hydroxyphenyl propionic acid) and indoles that act as anti-oxidants and anti-inflammatory agents, which improve immunity and gut barrier homeostasis [40,[49][50][51][52]. Indeed, the most predominant metabolite in our study is lactic acid: a result of the fermentation of rice by the LAB group bacteria.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Recent studies on fermented foods by the LAB group have also reported the presence of polyphenols (4-hydroxyphenyl propionic acid) and indoles that act as anti-oxidants and anti-inflammatory agents, which improve immunity and gut barrier homeostasis [40,[49][50][51][52]. Indeed, the most predominant metabolite in our study is lactic acid: a result of the fermentation of rice by the LAB group bacteria.…”
Section: Discussionsupporting
confidence: 57%
“…Our study identifies a rich and diverse range of postbiotic metabolites even in the short duration of simple natural fermentation of edible rice ( Figure 2 A and Table S2 ). Recent studies on fermented foods by the LAB group have also reported the presence of polyphenols (4-hydroxyphenyl propionic acid) and indoles that act as anti-oxidants and anti-inflammatory agents, which improve immunity and gut barrier homeostasis [ 40 , 49 , 50 , 51 , 52 ]. Indeed, the most predominant metabolite in our study is lactic acid: a result of the fermentation of rice by the LAB group bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Mushrooms are a rich source of valuable compounds with various biological effects, including antioxidant and anti-inflammatory effects [21]. Additionally, their composition of multiple compounds with synergistic effects modulates the colon microbiota and positively impacts the human body's homeostasis [2].…”
Section: Discussionmentioning
confidence: 99%
“…The microbiotas were obtained from the ColHumB Collection of the Laboratory of Pharmaceutical Biotechnologies, UASVM Bucharest (www.gissystems.ro). The experimental methodology followed the ethical criteria of the UASVM Bucharest (ColHumB Registration number: 1418/23 November 2017 [21]). The microbiota samples, which reflect the number of microorganisms, were preserved in a freezer using a solution of 20% glycerol until they were ready to be analyzed.…”
Section: In Vitro Modulation Of D2t-associated Microbiotamentioning
confidence: 99%